Adopcja w kodeksie z Gortyny - Rominkiewicz, Jarosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article is devoted to regulations concerning adoption, written in the so-called Code of Gortyn, founded in the first half of the 5th century BC. First, the author made a translation of a fragment of the Code which contained provisions relating to adoption. Then, he discussed the terminology for the institution and the qualifications the adopters and adoptees needed to meet. The rest of the article deals with the form of adoption, the legal consequences of this act, cancellation of the act and the confirmation of property rights acquired by the adoptee prior to the announcement of the Code. Wherever possible, the author showed differences and similarities between the Code of Gortyn and Athenian regulations. In the conclusion, he stressed that the position of an adopted son was not as strong as the position of the sons born in wedlock. He was not, in contrast to the former, made heir to his parents’ properties. He also did not have as strong a position as an adopted son in Athens. Athenian law did not diversify the situation of children born in wedlock gnesioi and those adopted. They both inherited the same part of the property. In Gortyn the adoptee who had adoptive brothers and sisters inherited equally with the latter, hence half of the property was inherited by a legitimate son.
Keywords: adopcja; kodeks prawny Gortyny; Gortyna